International Tourism (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Tourism, the act and process of spending time away from home in pursuit of recreation, relaxation, and pleasure, while making use of the commercial provision of services. As such, tourism is a product of modern social arrangements, beginning in western Europe in the 17th century, although it has antecedents in Classical antiquity.